Significance of coexistent granulomatous inflammation and lung cancer. Issue 4 (19th September 2016) - Dagaonkar, Rucha S; Choong, Caroline V; Asmat, Atasha Binti; Ahmed, Dokeu Basheer A; Chopra, Akhil; Lim, Albert Y H; Tai, Dessmon Y H; Kor, Ai Ching; Goh, Soon Keng; Abisheganaden, John; Verma, Akash
Abstract : Aims: Coexistence of lung cancer and granulomatous inflammation in the same patient confuses clinicians. We aimed to document the prevalence, clinicopathological features, treatment outcomes and prognosis in patients with coexisting granulomatous inflammation undergoing curative lung resection for lung cancer, in a tuberculosis (TB)-endemic country. Methods: An observational cohort study of patients with lung cancer undergoing curative resection between 2012 and 2015 in a tertiary centre in Singapore. Results: One hundred and twenty-seven patients underwent lung resection for cancer, out of which 19 (14.9%) had coexistent granulomatous inflammation in the resected specimen. Median age was 68 years and 58.2% were males. Overall median (range) survival was 451 (22–2452) days. Eighteen (14%) patients died at median duration of 271 days after surgery. The postsurgery median survival for those alive was 494 (29–2452) days in the whole group. Subgroup analysis did not reveal any differences in age, gender, location of cancer, radiological features, type of cancer, chemotherapy, history of TB or survival in patients with or without coexistent granulomatous inflammation. Conclusions: Incidental detection of granulomatous inflammation in patients undergoing lung resection for cancer, even in a TB-endemic country, may not require any intervention. Such findings may be due to either mycobacterial infection in the past or 'sarcoid reaction' to cancer. Although all patients should have their resected specimen sent for acid-fast bacilli culture and followed up until the culture results are reported, the initiation of the management of such patients as per existing lung cancer management guidelines does not affect their outcome adversely.